A methodology to link national and local information for spatial targeting of ammonia mitigation efforts. (September 2017) - Carnell, E.J.; Misselbrook, T.H.; Dore, A.J.; Sutton, M.A.; Dragosits, U.
Abstract: The effects of atmospheric nitrogen (N) deposition are evident in terrestrial ecosystems worldwide, with eutrophication and acidification leading to significant changes in species composition. Substantial reductions in N deposition from nitrogen oxides emissions have been achieved in recent decades. By contrast, ammonia (NH3 ) emissions from agriculture have not decreased substantially and are typically highly spatially variable, making efficient mitigation challenging. One solution is to target NH3 mitigation measures spatially in source landscapes to maximize the benefits for nature conservation. The paper develops an approach to link national scale data and detailed local data to help identify suitable measures for spatial targeting of local sources near designated Special Areas of Conservation (SACs). The methodology combines high-resolution national data on emissions, deposition and source attribution with local data on agricultural management and site conditions. Application of the methodology for the full set of 240 SACs in England found that agriculture contributes ∼45 % of total N deposition. Activities associated with cattle farming represented 54 % of agricultural NH3 emissions within 2 km of the SACs, making them a major contributor to local N deposition, followed by mineral fertiliser application (21 %). Incorporation of local information on agricultural management practices at seven example SACs provided the means to correct outcomes compared with national-scale emission factors. The outcomes show how national scale datasets can provide information on N deposition threats at landscape to national scales, while local-scale information helps to understand the feasibility of mitigation measures, including the impact of detailed spatial targeting on N deposition rates to designated sites. Highlights: An approach to identify suitable NH3 mitigation measures is proposed. The methodology combines emission, concentration and deposition data. Agriculture contributes ∼45% of total N deposition received by SACs.